Scavenging opportunities modulate escape responses over a small geographic scale - Fleming, P.; Bateman, Bill (Wiley-Blackwell Verlag GmbH, 2017)
Many species that inhabit anthropogenically altered landscapes also opportunistically use human food refuse. Gulls readily exploit anthropogenic food sources (e.g. rubbish dumps and other places of human refuse) and often ‘steal’ food from people eating out of doors. Their behaviour suggests that gulls perceive little risk around people and so we examined whether opportunity costs, that is access to anthropogenic food sources, influence risk monitoring and escape responses in Silver Gulls (Chroicocephalus novaehollandiae) around outdoor restaurants (‘food’ sites), where the gulls would scavenge food from people. We recorded alert distance (AD) and flight initiation distance (FID) and compared them with nearby sites where the same cohort of gulls was not interacting with people (‘no-food’ sites). We used two approach speeds (with the prediction that gulls would take greater efforts to avoid a potential predation threat when approached at speed). Gulls foraging at food sites had lower AD and FID than those approached at no-food sites. They were not simply ignoring the person, as they demonstrated longer AD when approached at speed but no difference in FID and therefore appeared to be responding to a small geographic scale ‘behavioural footprint’ of anthropogenic influences. Our study also challenges universality of the assumption that starting distance is necessarily correlated with FID, especially in sites where there are many people that animals are constantly monitoring – to determine the risk they represent as well as the likelihood of potential food opportunities.